OSCILLATING, NONEQUILIBRIUM REDOX PROPERTIES OF HUMIC ACIDS - Osterberg R.; Shirshova L. (My University, 1997)
Humic acids in solution behave as a kinetic system that is characterized by steady-states rather than by equilibria. This is shown by redox measurements at 0.1 M NaCl and 24°C under carefully controlled anaerobic conditions. When the humic acids were titrated with HCl from pH 6.4 to 3, the redox potential, after relaxation to a steady-state, showed a linear pH dependence with a slope of -42 mV/pH unit. (A supplementary study in a 0.1 M NaClO4 medium, using humic acids prepared from another source, agrees within the limits of experimental errors of +/-1 mV giving a slope of -44 mV/pH unit). In each titration point there was an initial, relatively fast relaxation with a tau-value within the range 150-400 s, followed by further slow relaxation (tau > 2.5 h) and/or oscillations, followed by arrival at a steady-state. This nonequilibrium behaviour implies the presence of polyphenolic residues, such as resorcinol, within the humic acid particles and their free radicals. In a redox diagram, the pH dependence of the apparent redox potential of humic acids is compared with the redox potential of various other redox pairs present in soil.